Evaluation of the application of essential oils as preservatives in the preparation of chorizo from Cuenca - Landines Vera, Edgar Fernando; Soledispa Chancay, Dayanna Narcisa (Ingeniería Química y Desarrollo, 2025)
The present work seeks to evaluate the application of essential oils as preservatives in the preparation of chorizo from Cuenca. Sausages, being processed meats seasoned with various aromatic herbs and spices introduced in a natural animal casing, have a high probability of germinating several pathogenic microorganisms in their manufacturing processes, so the application of rosemary and feijoa essential oils is justified since these are obtained from vegetable matter and have characteristics that originate aromas, light and very volatile that are obtained directly from plants, flowers, leaves, trees, roots, among others; that is why they have a very important role in the food industry to be applied for its antimicrobial activity that is why a study will be managed and / or conducted in a laboratory to the sample with greater acceptance where its microbiological and physicochemical progress is checked to demonstrate that it is suitable for consumption, in addition to obtaining the results shelf life which are 15 days according to the analysis that were conducted in the laboratory PROTAL.
Keywords: Rosemary; Feijoa; Chorizo cuencano; Essential oils; preservative; microbial